A dose‐dependent protective effect of n‐3 PUFAs in photoaging by promoting collagen production through MAPK pathway in SKH‐1 mouse model. (25th September 2022) - Xue, Huan; Shen, Shuzhan; Yan, Guorong; Yang, Yuling; Li, Jiandan; Kang, Ziwei; Cao, Yajing; Wang, Xiuli; Wang, Peiru
Abstract: Background: Dietary supplementation of n‐3 polyunsaturated fatty acids (n‐3 PUFAs) can inhibit inflammation and oxidation of photoaging, but the effect and mechanism on regulation of dermis collagen remains poorly elucidated. The destruction of dermal collagen plays a crucial role in the process of long‐term ultraviolet radiation (UVR) induced‐photoaging, especially leading to deterioration of skin appearance and function. Methods: In this study, we explored the protective effect of n‐3 PUFAs on the regulation of collagen through the MAPK pathway using the SKH‐1 photoaging mouse model. Results: The results showed that n‐3 PUFAs promoted collagen synthesis and reduced collagen degradation in a dose‐dependent manner, which was mediated by the down‐regulation of the MAPK pathway. In addition, n‐3 PUFAs supplementation inhibited the production of MMP‐1 and the UV‐induced abnormal proliferation of keratinocytes. All these effects resulted in the remodeling of extracellular matrix (ECM) and finally made a significant improvement in the appearance of skin. Conclusion: Overall, the present study suggested that dietary supplementation of n‐3 PUFAs has the potential clinical prospect to prevent UV‐induced skin damage and photoaging.